The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14202/vetworld.2017.716-720
|View full text |Cite
|
Sign up to set email alerts
|

Virulence gene profiles of Arcobacter species isolated from animals, foods of animal origin, and humans in Andhra Pradesh, India

Abstract: Aim::This study aimed to detect putative virulence genes in Arcobacter species of animal and human origin.Materials and Methods::A total of 41 Arcobacter isolates (16 Arcobacter butzleri, 13 Arcobacter cryaerophilus, and 12 Arcobacter skirrowii) isolated from diverse sources such as fecal swabs of livestock (21), raw foods of animal origin (13), and human stool samples (7) were subjected to a set of six uniplex polymerase chain reaction assays targeting Arcobacter putative virulence genes (ciaB, pldA, tlyA, mv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
4
18
1
Order By: Relevance
“…Furthermore, we detected cadF in 40% of isolates, which is in concordance with other studies reporting the presence of cadF in 10-62% of isolates [25,26,[28][29][30]]. While we were not able to detect any further virulence genes in A. cryaerophilus, other studies have reported the presence of cj1349 in 20-77% of isolates [25,26,[28][29][30], and also the genes hecB, hecA, and irgA were identified more often than in our study [25]. These differences might be due to the genomic heterogeneity in primer binding sequences.…”
Section: Virulence Genessupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we detected cadF in 40% of isolates, which is in concordance with other studies reporting the presence of cadF in 10-62% of isolates [25,26,[28][29][30]]. While we were not able to detect any further virulence genes in A. cryaerophilus, other studies have reported the presence of cj1349 in 20-77% of isolates [25,26,[28][29][30], and also the genes hecB, hecA, and irgA were identified more often than in our study [25]. These differences might be due to the genomic heterogeneity in primer binding sequences.…”
Section: Virulence Genessupporting
confidence: 92%
“…Our study revealed the abundance of ten putative virulence genes with homologies to virulence factors of other bacteria, particularly C. jejuni. In agreement with our data, six of these genes, i.e., ciaB, cj1349, cadF, tlyA, pldA, and mviN, have been detected most frequently in A. butzleri strains isolated from various sources, with prevalences ranging from 66 to 100% [11,23,[25][26][27][28][29][30][31]. We found hecB, hecA and irgA less frequently and at lower rates as compared to other reports [11,23,25,27,29,31,32].…”
Section: Virulence Genessupporting
confidence: 91%
“…Here, only strain G18RTA carried all 14 virulence genes associated with adherence, invasion, and iron uptake. This is consistent with previous reports, as it is very rare to find all virulence genes in every A. cryaerophilus isolate (Zacharow et al, 2015;Sekhar et al, 2017;Brückner et al, FIGURE 5 | Predicted virulence-associated determinants in 44 A. cryaerophilus genomes including 4 capsule genes, 8 chemotaxis system genes, 31 flagellar genes, 33 type IV secretion system genes, and other virulence determinants genes. 2020).…”
Section: In Silico Virulence Gene Profilingsupporting
confidence: 90%
“…In a previous study in South Africa, 6.5% of A. butzleri was reported [45]; additionally, percentages of 56.7% from diarrhoeic and 45.5% from non-diarrhoeic specimens were reported in Canada [56]. Virulence genes have been reported in A. butzleri in several studies [57][58][59].…”
Section: Prevalence Of Arcobactermentioning
confidence: 97%
“…The presence of these virulence genes in A. butzleri warranted the international commission of microbiological specification of foods (ICMSF) to categorize A. butzleri as a serious hazard to humans [59,60].…”
Section: Prevalence Of Arcobactermentioning
confidence: 99%